Padrões de ingestão e deslocamento de novilhas de corte em pastagens de estação fria - Sichonany, Maria José de Oliveira (2017)
The efficient use of pasture is associated to knowledge of the interactions between plant and herbivore, which includes the study of different plant characteristics resulting of had been grazed, which are defined by the grazing management, and the grazing strategies of the herbivore. A meta-analysis was made through a data base including eight experiments with the objective of studying and analyse the feeding behavior, displacement patterns, feeding stations use and meals dynamic of beef heifers (n=658) in cool season pastures. Data was stratified in: with or without energy supplement, phenological stages of grass (Vegetative, Pre-flowering, Flowering), shifts and hourly evaluations. The grazing time decreases and other activities time increases when beef heifers receive energy supplement at the level of 0.8% of body weight, keeping rumination time similar. The energy supplement fed for grazing heifers causes them to remain 12 min less at each feeding station. Supplemented heifers consumed 17.0% less forage and 22.2% less leaf blades than exclusively grazing heifers. Average daily gain of supplemented heifers is correlated positively with bite mass and number of steps between feeding stations. The heifers modify their ingestive behavior, bite rate, meal duration and interval between meals, forage selection patterns and number of steps per minute in the phenological stages of grass and evaluation shifts as a mechanism to keep bite mass similar. The grazing activity was concentrated in the afternoon shift, independent of the feeding system and the phenological stages, and in the night shift the longest rumination event occurs. The forage intake rate is independent of supplement intake and pasture phenological stages.